2020
DOI: 10.33546/bnj.1060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progressive Muscle Relaxation on Sleep Quality Among Patients With Chronic Diseases: A Literature Review

Abstract: Background: Sleep disturbance is prevalent among patients with chronic diseases. Thus, the use of non-pharmacological interventions is needed. Progressive muscle relaxation is considered effective to improve sleep quality, but its discussion is still limited.Objective: To investigate the effect of progressive muscle relaxation on sleep quality among chronic disease patients.Design: Literature review.Data Sources: Search was performed through the CINAHL, Science Direct, and ProQuest database from 2014 to 2019 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Progressive muscle relaxation can also lower pulse rate and blood pressure, as well as decrease sweating and respiratory rate. Muscle relaxation done regularly will have an anti-anxiety drug effect, and progressive muscle relaxation done for 20-30 minutes once a week is very effective in reducing insomnia [10], [13]- [18].…”
Section: Discussionmentioning
confidence: 99%
“…Progressive muscle relaxation can also lower pulse rate and blood pressure, as well as decrease sweating and respiratory rate. Muscle relaxation done regularly will have an anti-anxiety drug effect, and progressive muscle relaxation done for 20-30 minutes once a week is very effective in reducing insomnia [10], [13]- [18].…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] Another literature review focused on the effect of PMR on sleep quality among chronic disease patients reported that PMR significantly improves the sleep quality among patients with chronic diseases. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…[27] Another literature review focused on the effect of PMR on sleep quality among chronic disease patients reported that PMR significantly improves the sleep quality among patients with chronic diseases. [28] A rapid review on home-based activities that have potential beneficial effects on mental health have reported that exercise, yoga, PMR, and listening to relaxing music have beneficial effects on mental health. [7] A scoping review on mental health interventions implemented on COVID-19 patients revealed that telemonitoring, virtual games and strategies focused on social support and muscle relaxation techniques were shown as effective interventions.…”
Section: Jbi Critical Appraisal Checklist For Rctsmentioning
confidence: 99%
“…[13][14][15] Today, PRE are used to treat a variety of conditions, including, cancer, chronic pain, post-surgical pain, chronic fatigue, stress and anxiety, and women health physiotherapy. [16][17][18][19] In a randomized controlled study of women with PMS, PRE were found to lead to statistically significant reductions in depression and anxiety levels. [20] Furthermore, the Benson relaxation technique has been shown to produce significant improvements in physical and mental symptoms, as well as oxidative stress markers, in women with PMS.…”
Section: Introductionmentioning
confidence: 99%